A hard carbon negative electrode material and its preparation method and application

Through the fluidized cross-linking technology of asphalt and polymer cross-linking materials, a regular spherical hard carbon negative electrode material is formed, which solves the problems of low first efficiency and complex process in the existing technology, and achieves battery performance with high energy density and long cycle life .

CN116265390BActive Publication Date: 2025-01-17HUNAN SHINZOOM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111541944.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-16
Publication Date
2025-01-17
Estimated Expiration
2041-12-16

AI Technical Summary

Technical Problem

During the preparation process, existing hard carbon anode materials have problems such as low first efficiency, difficult to achieve regular spherical shape, high production costs, and complex processes, which are difficult to meet the needs of high energy density energy storage.

Method used

Asphalt and polymer crosslinking materials are used for fluidization and crosslinking, and a regular spherical structure is formed through primary temperature fluxation and secondary temperature fluxation, which reduces the specific surface area and improves tap density and electrochemical properties.

Benefits of technology

Achieve high first-term efficiency, capacity and rate performance improvement. The deliquification capacity at 0.1C can reach more than 468mAh/g, the first-term effect can reach more than 72%, and the capacity retention rate after 200 cycles can reach more than 72%. in lithium-ion and sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116265390B_ABST
    Figure CN116265390B_ABST
Patent Text Reader

Abstract

The present invention provides a hard carbon negative electrode material and a preparation method and application thereof. The raw materials of the hard carbon negative electrode material include asphalt material and polymer cross-linked material, and the morphology of the hard carbon negative electrode material is spherical and / or quasi-spherical. The preparation method includes the following steps: (1) mixing the polymer cross-linked material with the asphalt material, and shaping them to obtain a mixed material; (2) subjecting the mixed material to primary temperature rise fluidization, secondary temperature rise fluidization and carbon coating temperature rise fluidization in sequence to obtain a hard carbon negative electrode material; the primary temperature rise fluidization and secondary temperature rise fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature rise fluidization is carried out in a protective atmosphere. The hard carbon negative electrode material provided by the present invention has uniform particles and a rounded surface. The preparation method simultaneously realizes the cross-linking of the raw materials and the control of the morphology of the material, and does not require additional crushing and shaping processes, which effectively reduces the specific surface area of ​​the material, improves the tap density, and thus improves the first efficiency, capacity and rate performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of negative electrode materials and relates to a hard carbon negative electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are one of the most important rechargeable power sources at present. Graphite has become a common negative electrode for lithium-ion batteries due to its good crystallinity and layered structure. However, the theoretical capacity of the material is only 372mAh / g, which cannot meet the needs of human beings for high energy density energy storage. Carbon-based negative electrode materials have great research value. Among them, the theoretical capacity of hard carbon materials can reach 500mAh / g, which is mainly achieved by relying on the interlayer pore structure between the materials and the structure between the graphite layers to store lithium. However, due to some defective structures in the preparation process of the material, the material has a low initial efficiency during the first charge and discharge process, and it is difficult to obtain regular spherical hard carbon materials using conventional processes.

[0003] CN103311519A discloses a composite hard carbon negative electrode material and its preparation method and use, wherein: (i) crosslinking polymerization of asphalt to obtain a crosslinked body; (ii) the crosslinked body is solidified, crushed, graded, and pre-carbonized at low temperature to obtain a carbon precursor; (iii) the carbon precursor is crushed, graded, and then subjected to high-temperature carbonization to obtain carbonized particles; (iv) the carbonized particles are uniformly mixed with natural graphite at a mass ratio of 2:3 to 4:1. The capacity and coulomb efficiency of the composite hard carbon prepared by the above method are both low, and the reversible capacity is not high.

[0004] CN105293467A discloses a composite modified hard carbon negative electrode material prepared by dissolving, curing and ball milling phenolic resin, coal tar and phosphoric acid as raw materials. This method has the disadvantages of poor controllability of the preparation process, high production cost and difficulty in commercialization. CN102881869A discloses a modified hard carbon negative electrode material prepared by mixing, pyrolyzing and coating resin, flake graphite and boron phosphate as raw materials, but it also has the problems of low yield, complicated preparation process and difficulty in industrial production.

[0005] Therefore, how to obtain hard carbon negative electrode materials with regular morphology and no need for shaping, and with high initial efficiency, high capacity and high rate performance, is a technical problem that needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to provide a hard carbon negative electrode material and its preparation method and application. The present invention provides a hard carbon negative electrode material with a regular spherical shape, uniform particles and a rounded surface. By using asphalt as a reference material, the material is cross-linked with a polymer cross-linking material in a fluidized manner to simultaneously achieve cross-linking and control of the material's morphology, without the need for additional crushing and shaping processes, effectively reducing the material's specific surface area, increasing the tap density, and thereby improving the material's first efficiency, capacity and rate performance.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a hard carbon negative electrode material, wherein the raw materials of the hard carbon negative electrode material include an asphalt material and a polymer cross-linked material, and the morphology of the hard carbon negative electrode material is spherical and / or spherical-like.

[0009] The present invention provides a hard carbon negative electrode material with a regular spherical shape by using asphalt material and polymer cross-linking material as raw materials. The particles are uniform, the surface is rounded, the specific surface area is low, the tap density is high, and the first efficiency, capacity and rate performance of the material are improved.

[0010] Preferably, the tap density of the hard carbon negative electrode material is 0.7 to 1.0 g / cm 3 , for example 0.7 g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 or 1g / cm 3 wait.

[0011] Preferably, the polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two thereof.

[0012] In a second aspect, the present invention further provides a method for preparing the hard carbon negative electrode material as described in the first aspect, the preparation method comprising the following steps:

[0013] (1) mixing a polymer cross-linking material with an asphalt material, and molding the mixture to obtain a mixed material;

[0014] (2) subjecting the mixed material of step (1) to primary temperature-raising fluidization, secondary temperature-raising fluidization and carbon-coating temperature-raising fluidization in sequence to obtain the hard carbon negative electrode material;

[0015] The primary temperature-raising fluidization and the secondary temperature-raising fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature-raising fluidization is carried out in a protective atmosphere.

[0016] The present invention uses asphalt as the base material and simultaneously realizes cross-linking and control of the material morphology in a fluidized manner with a polymer cross-linking material, without the need for additional crushing and shaping processes. It effectively reduces the specific surface area of ​​the material, increases the tap density, and thereby improves the initial efficiency, capacity, and rate performance of the material.

[0017] In the present invention, during the first heating and fluidizing process, in an oxygen-containing atmosphere, the internal structure of the particles changes, and some small molecular aromatic structures overflow and volatilize under the action of heat. Under the action of oxygen and high molecular cross-linking materials, the aromatic ring structure inside the asphalt material can be interfered and rearranged to form an isotropic amorphous carbon structure, thereby improving the fast charging performance of the material. During the second heating and fluidizing process, the surface of the asphalt particle material will melt, and at the same time, under the action of strong airflow, the material is in a state of continuous motion, so the surface of the material will undergo a continuous shaping process to form a spherical structure with a rounded surface, and under the action of oxygen, the interior of the particles is further cross-linked to form a stable amorphous carbon structure. Further carbon coating and heating fluidization are carried out to deposit a uniform amorphous carbon structure on the surface of the material, effectively reducing the specific surface area of ​​the material and improving the initial efficiency of the material.

[0018] In the present invention, if the primary temperature-raising fluidization and the secondary temperature-raising fluidization are not carried out in an oxygen-containing atmosphere, the cross-linking of the internal molecular structure of the asphalt cannot be achieved.

[0019] In the present invention, if the secondary temperature-raising fluidization process is not performed, it is difficult to obtain a regular spherical carbon structure.

[0020] In the present invention, the use of a polymer cross-linking material and an asphalt material for cross-linking is more conducive to improving the internal cross-linking structure of the material and constructing a stable amorphous carbon structure.

[0021] Preferably, in step (1), the mass ratio of the polymer cross-linking material to the asphalt material is (0.2-2):1, for example, 0.2:1, 0.5:1, 1:1, 1.5:1 or 2:1, etc.

[0022] In the present invention, the mass ratio of the polymer cross-linking material to the asphalt material is too large, which is not conducive to improving the residual carbon value of the material and increases the material cost.

[0023] Preferably, the median particle sizes of the polymer cross-linked material and the asphalt material in step (1) are independently <5 μm, for example, 4.9 μm, 4.5 μm, 4 μm, 3.8 μm, 3.5 μm, 3.2 μm, 3 μm, 2.5 μm, 2 μm, 1.5 μm or 1 μm, etc.

[0024] Preferably, the softening point of the asphalt material in step (1) is 60-400°C, for example, 60°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C or 400°C.

[0025] Preferably, the polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two thereof.

[0026] Preferably, the forming in step (1) comprises isostatic pressing or cold pressing.

[0027] Preferably, the material formed in step (1) is crushed.

[0028] Preferably, the median particle size of the mixed material in step (1) is 5 to 20 μm, for example 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0029] Preferably, the temperature of the first heating and fluidization in step (2) is 250-400°C, for example, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, etc.

[0030] In the present invention, if the temperature of the first heating and fluidization in step (2) is too low, it will lead to incomplete crosslinking reaction, while if the temperature of the first heating and fluidization is too high, it will lead to excessive volatile matter, which is not conducive to increasing the residual carbon value of the material.

[0031] Preferably, the time for the first heating and fluidization in step (2) is 3 to 12 hours, for example, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours or 12 hours.

[0032] Preferably, the heating rate of the secondary heating and fluidization in step (2) is 0.5 to 3°C / min, for example, 0.5, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min.

[0033] In the present invention, the heating rate of the secondary heating fluidization is too fast, which is not conducive to the shaping of the spherical structure.

[0034] Preferably, the temperature of the secondary heating and fluidization in step (2) is 500-600°C, for example, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, 560°C, 570°C, 580°C, 590°C or 600°C.

[0035] In the present invention, during the secondary heating and fluidizing process, if the temperature is too low, it is not conducive to the softening treatment of the surface structure of the spherical structure, and if the temperature is too high, it will cause the material to coke and the spherical structure cannot be formed subsequently.

[0036] Preferably, the time of the secondary temperature rise and fluidization in step (2) is 1 to 5 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0037] Preferably, the carbon coating heating and fluidization in step (2) is carried out by gas phase carbon coating.

[0038] Preferably, the heating rate of the carbon coating heating and fluidization in step (2) is 1 to 5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min.

[0039] Preferably, the temperature of the carbon coating heating and fluidization in step (2) is 800-1200°C, for example, 800°C, 900°C, 1000°C, 1100°C or 1200°C.

[0040] Preferably, the carbon coating heating and fluidization time in step (2) is 2 to 6 hours, for example, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours.

[0041] As a preferred technical solution, the preparation method comprises the following steps:

[0042] (1) mixing the polymer cross-linking material and the asphalt material at a mass ratio of (0.2-2):1, forming, and crushing to obtain a mixed material with a median particle size of 5-20 μm;

[0043] (2) heating the mixed material in step (1) to 250-400° C. for a primary heating and fluidization for 3-12 h, then heating the mixed material to 500-600° C. at a heating rate of 0.5-3° C. / min for a secondary heating and fluidization for 1-5 h, and finally heating the mixed material to 800-1200° C. at a heating rate of 1-5° C. / min for carbon coating and fluidization for 2-6 h in the form of gas-phase carbon coating to obtain the hard carbon negative electrode material;

[0044] Wherein, the median particle size of the polymer cross-linking material and the asphalt material in step (1) is independently <5 μm; the softening point of the asphalt material in step (1) is 60-400°C; the polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two thereof; the molding in step (1) includes isostatic pressing or cold pressing; the primary temperature rising fluidization and the secondary temperature rising fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature rising fluidization is carried out in a protective atmosphere.

[0045] In a third aspect, the present invention further provides a battery, wherein the battery comprises the hard carbon negative electrode material as described in the first aspect, and the battery comprises a lithium ion battery and / or a sodium ion battery.

[0046] The hard carbon negative electrode material provided by the present invention has a wide range of applications, not only applicable to lithium ion batteries, but also applicable to sodium ion batteries.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The present invention provides a hard carbon negative electrode material with a regular spherical shape, which has uniform particles and a rounded surface. By using asphalt as a reference material, cross-linking and material morphology control are simultaneously achieved in a fluidized manner with a polymer cross-linking material, without the need for additional crushing and shaping processes, which effectively reduces the specific surface area of ​​the material, improves the tap density, and thus improves the first efficiency, capacity and rate performance of the material. The battery provided by the present invention has a lithium removal capacity of more than 468 mAh / g at 0.1C, a first efficiency of more than 72%, and a capacity retention of more than 5C / 0.5C. The capacity retention rate can reach more than 36%, and the capacity retention rate after 200 cycles can reach more than 72%. The mass ratio of the polymer cross-linking material to the asphalt material is further made within the range of (0.2-2):1, and the primary heating and fluidizing temperature is within the range of 250-400°C, and the secondary heating and fluidizing temperature is within the range of 500-600°C. The lithium desorption capacity of the battery at 0.1C can reach more than 506mAh / g, the first efficiency can reach more than 83%, the capacity retention rate of 5C / 0.5C can reach more than 42%, and the capacity retention rate after 200 cycles can reach more than 83%. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is the SEM image of the hard carbon negative electrode material provided in Example 1. DETAILED DESCRIPTION

[0050] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0051] Example 1

[0052] This embodiment provides a hard carbon negative electrode material with a spherical surface morphology.

[0053] The preparation method of the hard carbon negative electrode material is as follows:

[0054] (1) phenolic resin (median particle size of 3.6 μm) and coal tar pitch (median particle size of 4 μm, softening point of 200° C.) were mixed in a mass ratio of 1:1, placed in an isostatic pressing device for block molding (molding), and then the material was crushed to obtain a mixed material with a median particle size of 13 μm;

[0055] (2) Placing the mixed material described in step (1) on a fluidized bed, and placing the particles in an air atmosphere in a fluidized state, then heating the equipment to 300°C for a first temperature rise and fluidization for 6 hours, and then continuing to heat the air atmosphere to 550°C at a heating rate of 2°C / min for a second temperature rise and fluidization for 3 hours. After the temperature rise and fluidization, switch to an argon atmosphere and introduce acetylene at the same time, and heat the temperature to 1200°C at a heating rate of 5°C / min for carbon coating and fluidization for 4 hours to obtain the hard carbon negative electrode material.

[0056] Figure 1 The SEM image of the hard carbon negative electrode material provided in Example 1 is shown. Figure 1 It can be seen that the hard carbon negative electrode material is in a regular spherical shape. It can be concluded that, through the preparation method provided by the present invention, a hard carbon negative electrode material with a regular morphology without the need for additional shaping is prepared.

[0057] Example 2

[0058] This embodiment provides a hard carbon negative electrode material with a spherical surface morphology.

[0059] The preparation method of the hard carbon negative electrode material is as follows:

[0060] (1) polyvinyl alcohol (median particle size of 2 μm) and petroleum asphalt (median particle size of 3.5 μm, softening point of 250° C.) were mixed in a mass ratio of 0.2:1, placed in an isostatic pressing device for block molding, and then the material was crushed to obtain a mixed material with a median particle size of 12 μm;

[0061] (2) The mixed material of step (1) is placed on a fluidized bed, and the particles are fluidized under air atmosphere. The equipment is then heated to 250°C for a first heating and fluidization for 12 hours, and then the temperature is continued to be increased to 500°C at a heating rate of 0.5°C / min under air atmosphere for a second heating and fluidization for 5 hours. After the temperature is increased, the atmosphere is switched to argon gas, and methane is introduced at the same time. The temperature is increased to 800°C at a heating rate of 1°C / min for carbon coating and fluidization for 6 hours to obtain the hard carbon negative electrode material.

[0062] Example 3

[0063] This embodiment provides a hard carbon negative electrode material with a spherical surface morphology.

[0064] The preparation method of the hard carbon negative electrode material is as follows:

[0065] (1) polyacrylonitrile (median particle size of 4 μm) and petroleum asphalt (median particle size of 4.9 μm, softening point of 300°C) were mixed in a mass ratio of 2:1, placed in a cold press for block molding, and then the material was crushed to obtain a mixed material with a median particle size of 9 μm;

[0066] (2) The mixed material of step (1) is placed on a fluidized bed, and the particles are fluidized under air atmosphere. The equipment is then heated to 400°C for a first heating and fluidization for 3 hours, and then the temperature is continued to be heated to 600°C at a heating rate of 3°C / min under air atmosphere for a second heating and fluidization for 1 hour. After the temperature is switched to argon atmosphere, acetylene is introduced at the same time, and the temperature is heated to 1050°C at a heating rate of 3°C / min for carbon coating and fluidization for 8 hours to obtain the hard carbon negative electrode material.

[0067] Example 4

[0068] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, the mass ratio of phenolic resin to coal tar is 2.5:1.

[0069] The rest of the preparation methods and parameters were the same as those in Example 1.

[0070] Example 5

[0071] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the first heating and fluidization is 200°C.

[0072] The rest of the preparation methods and parameters were the same as those in Example 1.

[0073] Example 6

[0074] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the secondary heating and fluidization is 450°C.

[0075] The rest of the preparation methods and parameters were the same as those in Example 1.

[0076] Example 7

[0077] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the secondary heating and fluidization is 650°C.

[0078] The rest of the preparation methods and parameters were the same as those in Example 1.

[0079] Comparative Example 1

[0080] The difference between this comparative example and Example 1 is that in step (2) of this comparative example, no secondary temperature rise and fluidization is performed, that is, the carbon coating temperature rise and fluidization is performed directly after the primary temperature rise and fluidization.

[0081] The rest of the preparation methods and parameters were the same as those in Example 1.

[0082] Comparative Example 2

[0083] This comparative example provides a hard carbon negative electrode material, and the preparation method of the hard carbon negative electrode material is as follows:

[0084] Using glucose as raw material, glucose was dissolved in water and added into a polytetrafluoroethylene container, which was then sealed for hydrothermal reaction at a heating temperature of 180°C for 6 hours. It was then washed and dried, and then carbonized at 1000°C to obtain a spherical hard carbon material.

[0085] Table 1 shows the median particle size and tap density of the hard carbon negative electrode materials provided by Examples 1-7 and Comparative Examples 1-2.

[0086] Table 1

[0087] Median particle size (μm) <![CDATA[Tap density (g / cm 3 ) <!-- 5 -->]]> Example 1 12.5 0.86 Example 2 12.7 0.88 Example 3 12.4 0.85 Example 4 12.9 0.75 Example 5 12.4 0.83 Example 6 13.1 0.75 Example 7 13.2 0.72 Comparative Example 1 13.1 0.65 Comparative Example 2 4 0.81

[0088] It can be seen from Table 1 that the hard carbon negative electrode material provided by the present invention will form a regular morphology during the continuous fluidization process, resulting in a higher tap density of the material and better powder processing performance.

[0089] The hard carbon negative electrode material, conductive carbon black, SBR and CMC provided by Example 1-7 and Comparative Example 1-2 were mixed in a mass ratio of 95:2:1.5:1.5 to obtain a negative electrode slurry, which was coated on the surface of a copper foil, dried and rolled to obtain a pole sheet, and a lithium sheet was used as a counter electrode to obtain a button-type lithium-ion battery.

[0090] The electrochemical performance test of the batteries provided in Examples 1-7 and Comparative Examples 1-2 was performed under the following test conditions:

[0091] Electrochemical performance test: The obtained hard carbon negative electrode material was evenly mixed with SBR, CMC, and SP in a ratio of 94.5:2.5:1.5:1.5, coated on copper foil, and prepared into a pole piece with a diameter of 12 mm after drying, rolling, and cutting. It was assembled into a button battery with a metal lithium sheet, in which the electrolyte was a conventional lithium-ion battery electrolyte and the diaphragm was a PP diaphragm.

[0092] The battery capacity (the lithium desorption capacity of the battery at 0.1C, the voltage range is 0.05-2V), the first-week efficiency, the rate (the capacity retention rate of 5C / 0.5C) and the cycle performance (the capacity retention rate of the battery after 200 cycles of 0.5C / 0.5C charge and discharge), where 1C=400mAh / g, were tested using a blue electric tester, and the results are shown in Table 1.

[0093] Table 1

[0094]

[0095] It can be seen from the data results of Example 1 and Example 4 that if the mass proportion of the polymer cross-linked material is too large, it will cause the internal polymer proportion to be too high, reduce the initial effect of the material, and affect the cyclic stability of the material.

[0096] It can be seen from the data results of Example 1 and Example 5 that if the temperature of the first heating and fluidization is too low, it is difficult to achieve internal cross-linking of the asphalt material, which will lead to a decrease in the rate performance and cycle performance of the material.

[0097] From the data results of Examples 1, 6 and 7, it can be seen that if the temperature of the secondary heating fluidization is too low, it is not conducive to the shaping of spherical particles. If the temperature is too high, it will lead to excessive loss of volatiles inside the asphalt, causing coking, thereby affecting the electrochemical properties of the material.

[0098] It can be seen from the data results of Example 1 and Comparative Example 1 that without the secondary temperature increase and fluidization process, the shaping of the material particles cannot be achieved, which reduces the electrochemical performance of the material.

[0099] It can be seen from the data results of Example 1 and Comparative Example 2 that, compared with the conventional preparation method of hard carbon negative electrode materials, the preparation method provided by the present invention can well realize the preparation of high-capacity and high-initial-efficiency hard carbon materials, and the preparation method of Comparative Example 2 is complicated and has a low yield, which leads to an increase in the overall cost and is not conducive to production and large-scale application.

[0100] In summary, the present invention provides a hard carbon negative electrode material with a regular spherical shape, which has uniform particles and a rounded surface. By using asphalt as the base material, the material is cross-linked with a polymer cross-linking material in a fluidized manner to simultaneously achieve cross-linking and control of the material's morphology, without the need for additional crushing and shaping processes, thereby effectively reducing the material's specific surface area, increasing the tap density, and thereby increasing the material's first efficiency, capacity, and rate performance. The battery provided by the present invention has a lithium removal capacity of more than 468 mAh / g at 0.1C, a first efficiency of more than 72%, and a capacity of 5C / 0.5C. The capacity retention rate can reach more than 36%, and the capacity retention rate after 200 cycles can reach more than 72%. The mass ratio of the polymer cross-linking material to the asphalt material is further made within the range of (0.2-2):1, and the first heating fluidization temperature is within the range of 250-400°C, and the second heating fluidization temperature is within the range of 500-600°C. The lithium desorption capacity of the battery at 0.1C can reach more than 506mAh / g, the first efficiency can reach more than 83%, the capacity retention rate of 5C / 0.5C can reach more than 42%, and the capacity retention rate after 200 cycles can reach more than 83%.

[0101] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A hard carbon negative electrode material, characterized in that: The raw materials of the hard carbon negative electrode material include asphalt material and polymer cross-linked material, and the morphology of the hard carbon negative electrode material is spherical and / or spherical-like; The method for preparing the hard carbon negative electrode material comprises the following steps: (1) mixing a polymer cross-linking material with an asphalt material, and molding the mixture to obtain a mixed material; (2) subjecting the mixed material of step (1) to primary temperature-raising fluidization, secondary temperature-raising fluidization and carbon-coating temperature-raising fluidization in sequence to obtain the hard carbon negative electrode material; The primary temperature-raising fluidization and the secondary temperature-raising fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature-raising fluidization is carried out in a protective atmosphere; In step (1), the mass ratio of the polymer cross-linking material to the asphalt material is (0.2-2):1; The temperature of the first heating and fluidization in step (2) is 250-400° C.; The temperature of the secondary heating and fluidization in step (2) is 500-600° C. The carbon coating in step (2) is carried out by heating and fluidizing the carbon coating using a gas phase carbon coating method.

2. The hard carbon negative electrode material according to claim 1, characterized in that: The tap density of the hard carbon negative electrode material is 0.7 to 1.0 g / cm 3 .

3. The hard carbon negative electrode material according to claim 1, characterized in that: The polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two of them.

4. A method for preparing a hard carbon negative electrode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a polymer cross-linking material with an asphalt material, and molding the mixture to obtain a mixed material; (2) subjecting the mixed material of step (1) to primary temperature-raising fluidization, secondary temperature-raising fluidization and carbon-coating temperature-raising fluidization in sequence to obtain the hard carbon negative electrode material; The primary temperature-raising fluidization and the secondary temperature-raising fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature-raising fluidization is carried out in a protective atmosphere.

5. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: In step (1), the median particle sizes of the polymer cross-linking material and the asphalt material are independently <5 μm.

6. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The softening point of the asphalt material in step (1) is 60-400°C.

7. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two of them.

8. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The forming in step (1) includes isostatic pressing or cold pressing.

9. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The material formed in step (1) is crushed.

10. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The median particle size of the mixed material in step (1) is 5 to 20 μm.

11. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The time for the first heating and fluidization in step (2) is 3 to 12 hours.

12. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The heating rate of the secondary heating and fluidization in step (2) is 0.5 to 3°C / min.

13. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The time of the secondary heating and fluidization in step (2) is 1 to 5 hours.

14. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The heating rate of the carbon coating heating and fluidization in step (2) is 1 to 5°C / min.

15. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The temperature of the carbon coating heating and fluidization in step (2) is 800-1200°C.

16. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The carbon coating heating and fluidization time in step (2) is 2 to 6 hours.

17. The method for preparing a hard carbon negative electrode material according to claim 4, characterized in that: The preparation method comprises the following steps: (1) mixing the polymer cross-linking material and the asphalt material at a mass ratio of (0.2-2):1, forming, and crushing to obtain a mixed material with a median particle size of 5-20 μm; (2) heating the mixed material in step (1) to 250-400° C. for a primary heating and fluidization for 3-12 h, then heating the mixed material to 500-600° C. at a heating rate of 0.5-3° C. / min for a secondary heating and fluidization for 1-5 h, and finally heating the mixed material to 800-1200° C. at a heating rate of 1-5° C. / min for carbon coating and fluidization for 2-6 h in the form of gas-phase carbon coating to obtain the hard carbon negative electrode material; Wherein, the median particle size of the polymer cross-linking material and the asphalt material in step (1) is independently <5 μm; the softening point of the asphalt material in step (1) is 60-400°C; the polymer cross-linking material includes any one of phenolic resin, epoxy resin, polyvinyl alcohol, polystyrene, polyacrylonitrile, polyethylene or polyamide, or a combination of at least two thereof; the molding in step (1) includes isostatic pressing or cold pressing; the primary temperature rising fluidization and the secondary temperature rising fluidization are carried out in an oxygen-containing atmosphere, and the carbon coating temperature rising fluidization is carried out in a protective atmosphere.

18. A battery, characterized in that: The battery comprises the hard carbon negative electrode material according to any one of claims 1 to 3, and the battery comprises a lithium ion battery and / or a sodium ion battery.

Citation Information

Patent Citations

  • Modified hard carbon negative electrode material for lithium ion battery and preparation method for modified hard carbon negative electrode material

    CN102881869A

  • Composite hard carbon negative electrode material, and preparation method and application thereof

    CN103311519A

  • Phenolic resin / coal tar pitch composite-base modified hard carbon negative electrode material and preparation method and application thereof

    CN105293467A

  • Preparation method and modification method of hard carbon negative electrode material for lithium ion power batteries

    CN106981629A